Development and evaluation of human T‐cell leukemia virus‐1 and ‐2 multiplex quantitative PCR. (11th September 2019) - Kuramitsu, Madoka; Okuma, Kazu; Tezuka, Kenta; Nakamura, Hitomi; Sagara, Yasuko; Kurane, Ichiro; Hamaguchi, Isao
Abstract: The diagnosis of human T ‐cell leukemia virus type 1 (HTLV‐1) infection in Japan is usually performed by serological testing, but the high rate of indeterminate results from western blotting makes it difficult to assess the infection accurately. Nucleic acid tests for HTLV‐1 and/or HTLV‐2 are used to confirm infection with HTLV‐1 and/or HTLV‐2 and are also used for the follow‐up of HTLV‐1 related diseases. To prepare a highly sensitive method that can discern infection with HTLV‐1 and HTLV‐2, a multiplex quantitative polymerase chain reaction (qPCR) by large‐scale primer screening was developed. Sensitivity and specificity were evaluated by serial dilution of cell lines and by testing with known clinical samples. The resulting multiplex qPCR can detect about four copies of HTLV‐1 provirus per 10 5 cells. Moreover, HTLV‐1 provirus could be detected in 97.2% (205 of 211) of HTLV‐1 seropositive clinical samples. These sensitivities were sufficiently high compared with the methods reported previously. Also, all the HTLV‐2 seropositive clinical samples tested were found to be positive by this method (three of three). In conclusion, this method can successfully and simultaneously detect both types of HTLV‐1 and HTLV‐2 provirus with extremely high sensitivity.